New Records of Helminth Parasites in Amphibians from the South American Chaco - M. A. González; M. A. Villegas Ojeda; J. N. Caraballo; L. G. Ailán Choke; M. I. Hamann; M. I. Duré; V. I. Gómez; C. E. González (Zoodiversity, 2024)
This study aims to identify the helminth fauna of twelve anurans species from Argentina's Dry and Humid Chaco ecoregions. We collected one hundred and fifty-two specimens belonging to the species Dendropsophus nanus (n = 17), Scinax nasicus (n = 15), Pithecopus azureus (n = 7), Pseudis platensis (n = 10), Trachycephalus typhonius (n = 7) (Hylidae), Leptodactylus bufonius (n = 3), L. latinasus (n = 16), L. luctator (n = 14), L. macrosternum (n = 12), Physalaemus santafecinus (n = 14), P. albonotatus (n = 11) (Leptodactylidae), and Elachistocleis haroi (n = 26) (Microhylidae) from 3 areas located in the provinces of Chaco and Formosa (Dry Chaco) and in Corrientes province (Humid Chaco). A total of 17 helminth taxa were found; acanthocephalans in the larval stage (Centrorhynchidae: Centrorhynchus sp.) and nematodes in the larval stage (Anisakidae: Contracaecum; Ascarididae: Porrocaecum; Physalopteridae: Physaloptera; aff. Cystidicolidae) and adult stage (Rhabdiasidae: Rhabdias sp., R. elegans; Strongyloididae: Strongyloides pereirai; Molineidae: Oswaldocruzia proencai, O. subauricularis; Pharyngodonidae: Parapharyngodon senisfaciecaudus cubensis; Cosmocercidae: Aplectana hylambatis, Cosmocerca parva, C. podicipinus, Cosmocercella phyllomedusae, Schrankiana formosula; Kathlaniidae: Falcaustra mascula). This study presents new host and geographic records and expands knowledge of helminth diversity in a critically threatened group of vertebrates.